Augmented Reality-Based Fungi Encyclopedia: Validity and Practicality as a Biology Learning Media - Nurul Hidayati Utami; Aminuddin Prahatama Putra; Zaimuariffudin Shukri bin Nordin; M Arsyad (Journal of Mathematics Science and Computer Education, 2026)
Biology learning on the topic of macrofungi is often hindered by the abstract nature of the concepts and the reliance on static textbook illustrations. This condition is considered insufficient to represent the complexity of the three-dimensional morphology of fungal structures, resulting in low student engagement and limited conceptual understanding. To address this issue, this study aimed to develop FUNGARIA, an Augmented Reality (AR)-based macro fungi encyclopedia, and to evaluate its validity and practicality as a learning aid for promoting environmental literacy. The research employed the ADDIE development model (Analysis, Design, Development, Implementation, and Evaluation). Data were collected through validation by three experts (subject matter, media, and instructional design) using a 15-item four-point Likert scale instrument, as well as a practicality assessment conducted by experienced biology teachers through a 21-item questionnaire. FUNGARIA achieved an overall validity score of 83.33% (Highly Valid), confirming the product's feasibility in terms of mycological concept accuracy, alignment with Learning Outcomes, and the quality of the AR interface. In the practicality assessment, the media obtained a score of 95.44% (Highly Practical) across four evaluation dimensions: operational ease (94.79%), usability (95.42%), visual appearance and readability (95.83%), and educational benefits (95.83%). The novelty of this study lies in integrating the stability of printed guidance materials with immersive AR-based digital visualization to overcome limitations in device availability within schools.